2015
DOI: 10.1016/j.chembiol.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Lipoproteomics in Clostridium difficile Reveals a Role for Lipoproteins in Sporulation

Abstract: Bacterial lipoproteins are surface exposed, anchored to the membrane by S-diacylglyceryl modification of the N-terminal cysteine thiol. They play important roles in many essential cellular processes and in bacterial pathogenesis. For example, Clostridium difficile is a Gram-positive anaerobe that causes severe gastrointestinal disease; however, its lipoproteome remains poorly characterized. Here we describe the application of metabolic tagging with alkyne-tagged lipid analogs, in combination with quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…For example, the lgt mutant of Bacillus anthracis not only showed a decreased innate immune stimulation but also was affected in spore germination both in vitro and in mouse skin, which was most likely the reason for the markedly decreased virulence; on the other hand, vegetative cells of the lgt mutant still produced anthrax toxin, rendering the cells dangerous (45). In the anaerobe Clostridium difficile, which causes severe gastrointestinal disease, the lipoproteome was determined by an elegant detection method using alkyne-tagged lipid analogs (46). With this method, most of the predicted Lpp could be detected.…”
Section: Maturation Of Pre-lpp Is Crucial For Pathogenicity and Inflamentioning
confidence: 99%
“…For example, the lgt mutant of Bacillus anthracis not only showed a decreased innate immune stimulation but also was affected in spore germination both in vitro and in mouse skin, which was most likely the reason for the markedly decreased virulence; on the other hand, vegetative cells of the lgt mutant still produced anthrax toxin, rendering the cells dangerous (45). In the anaerobe Clostridium difficile, which causes severe gastrointestinal disease, the lipoproteome was determined by an elegant detection method using alkyne-tagged lipid analogs (46). With this method, most of the predicted Lpp could be detected.…”
Section: Maturation Of Pre-lpp Is Crucial For Pathogenicity and Inflamentioning
confidence: 99%
“…The spore-predominant ATPases include a cation (Ca 2+ )-transporting ATPase (CD2503), which shares 42% identity with B. subtilis YloB ATPase, likely responsible for accumulating intracellular calcium and reinforcing thermal resistance(51). Two ABC-type transporters - lipoproteins CD2365 and SsuA - are expressed in both C. difficile vegetative cells and spores (20) but are present at higher levels in spores. These are alkanesulfonate and taurine binding proteins, respectively and SsuA is involved in sulfur metabolism (52).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, a few transcriptomic studies (11, 12), quantitative proteomic studies (1319) and a lipoproteomic study (20) have been done on C. difficile vegetative cells. Lawley and colleagues described a protocol to purify spores and performed an extensive proteomic characterization of C. difficile 630 spores (21).…”
Section: Introductionmentioning
confidence: 99%
“…However, our laboratory has shown that alkyne reporters of long‐chain fatty acids (Figure A) can be metabolically incorporated into diverse bacterial species for profiling lipoproteins with canonical lipobox motifs (Figure B) as well as discovery of unpredicted fatty‐acylated proteins . Moreover, alkyne–fatty acid labeling of Gram‐positive bacteria by the Tate laboratory can reveal unique biosynthetic pathways such as the existence of two active signal peptidases in Clostridium difficile for lipoprotein biogenesis . In addition to labeling lipids and proteins within bacteria, the application of these fatty acid reporters can reveal host regulation of secreted bacterial virulence factors as well as host substrates of secreted bacterial enzymes during infection .…”
Section: Chemical Reporters For Microbiologymentioning
confidence: 99%
“…[68,69] ChemBioChem 2020, 21,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] www.chembiochem.org in Clostridium difficile for lipoprotein biogenesis. [73] In addition to labeling lipids and proteins within bacteria, the application of these fatty acid reporters can reveal host regulation of secreted bacterial virulencef actorsa sw ell as host substrates of secreted bacterial enzymes during infection. [74][75][76][77] Beyondc ovalent fatty acylation of bacterialp roteins, bifunctional fatty acid photoaffinity reporters can be used to crosslinka nd characterize noncovalent fatty acid interactions with proteins ( Figure 10 C).…”
Section: Lipid Reportersmentioning
confidence: 99%